ChemInform Abstract: Diterpene Constituents of Euphorbia exigua L. and Multidrug Resistance Reversing Activity of the Isolated Diterpenes. Issue 2 (23rd December 2015) - Redei, Dora; Boros, Klara; Forgo, Peter; Molnar, Joseph; Kele, Zoltan; Palinko, Istvan; Pinke, Gyula; Hohmann, Judit
Abstract: Two novel, (I) and (II), and one known jatrophane diterpene are isolated from the title species and evaluated for their multidrug resistance reversing activity.